Inovasi Pendidikan Al-Qur'an: Manajemen Pelatihan Satu Desa Satu Hafizh (Sadesha) Jawa Barat - Fathurrohman, Asep Ahmad; Mujib, Abdul (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2025)
The background of this research relates to the implementation of the Al-Quran teaching method in the One Village One Hafizh (Sadesha) Program in West Java Province, which aims to create 6000 hafizh-hafizhah by 2022. The program is expected to contribute to improving the quality of religious education and Quran teaching at the village level. This study aims to analyze the management of teaching methods applied in the program. The research method used is descriptive with a qualitative approach, which involves secondary data analysis in the form of annual reports and program-related documents, as well as interviews with relevant parties such as program coordinators and participants. The results showed that the management of the Sadesha program in West Java Province has been running well, in accordance with the established plan. The program uses two main strategies, namely empowerment and cadre, to achieve the target number of hafizh-hafizhah. Obstacles found related to the imbalance in the number of participants between districts/cities can be overcome through subsidies between districts/cities. The conclusion of this study is that the Sadesha program has successfully achieved its main objectives, with successes that can be used as a model for the development of similar programs in other regions. However, there are several obstacles that need to be overcome, such as the distribution of participants and honorarium issues, which require further attention to improve the program.